RELAŢIILE POLITICE ŞI ECONOMICE ALE REPUBLICII MOLDOVA CU REPUBLICA BELARUS (1991-2005) - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2009)
In the article are analyzed the political and economical relations of Republic of Moldova with the Republic of Belarus during 1991-2005. The author reveals the formation of the legal basis of multilateral cooperation between two countries. The political and economical relations between Republic of Moldova and Republic of Belarus did not evaluate constantly, it was signed many agreements, treaties, conventions which opened the way to a fruitful bilateral cooperation.